Enhancing wildfire response through drone selection: a BOCR-based multi-criteria approach - Tukenmez, I.; Kamisli Ozturk, Z. (Springer, 2025)
Forest fires have increased in recent years and have become an increasingly urgent problem, posing serious threats to ecosystems, infrastructure, and human life. The economic, sociological, and environmental impacts of such disasters highlight the urgency for innovative and effective solutions. One such approach involves the use of drones equipped with advanced capabilities, such as fire suppression systems, to increase the effectiveness of firefighting operations. However, selecting the most suitable drone for these tasks presents a multi-criteria decision-making challenge. This study employs the benefit-opportunity-cost-risk (BOCR) framework to evaluate drone alternatives, using the analytic hierarchy process (AHP) mehod to determine the relative weights of the criteria. Subsequently, the VIKOR method and the TOPSIS method, two multi-criteria decision-making methods, are applied to rank the alternatives and identify optimal solutions. By integrating multiple methods, this study ensures a comprehensive and robust evaluation process, contributing to the growing body of research on drone applications in disaster management and providing stakeholders with a structured framework for effective decision-making.
Keywords: Drone selection; MCDM; AHP; TOPSIS; VIKOR; Forest fire management